2022
DOI: 10.1038/s41467-022-29329-x
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive marsquakes in Martian upper mantle

Abstract: Marsquakes excite seismic wavefield, allowing the Martian interior structures to be probed. However, the Martian seismic data recorded by InSight have a low signal-to-noise ratio, making the identification of marsquakes challenging. Here we use the Matched Filter technique and Benford’s Law to detect hitherto undetected events. Based on nine marsquake templates, we report 47 newly detected events, >90% of which are associated with the two high-quality events located beneath Cerberus Fossae. They occurred at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 58 publications
(99 reference statements)
0
20
0
1
Order By: Relevance
“…Something like this can be caused by a volume of magma that propagates as a dike intrusion, then cools, stalls, or partially deflates some seconds later, activating slip on fractures or faults in surrounding rock. A recent analysis by Sun and Tkalčić (2022) found many marsquakes in the area of Cerberus Fossae, many of which have smaller signal to noise ratios than S0173a but contain similar waveforms. Based on this repetitive nature of the seismicity, Sun and Tkalčić (2022) concluded that a magmatic origin was the most likely explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Something like this can be caused by a volume of magma that propagates as a dike intrusion, then cools, stalls, or partially deflates some seconds later, activating slip on fractures or faults in surrounding rock. A recent analysis by Sun and Tkalčić (2022) found many marsquakes in the area of Cerberus Fossae, many of which have smaller signal to noise ratios than S0173a but contain similar waveforms. Based on this repetitive nature of the seismicity, Sun and Tkalčić (2022) concluded that a magmatic origin was the most likely explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Our detection method is only limited by the availability of 20 sps data set from the VBB sensor-but could also be modified to run on 10 sps data and recordings from the SP sensor after retraining. Sun and Tkalčić (2022) reported the discovery of 47 new LF events found during both the low-and high noise periods with template matching techniques using the S-wave waveform of nine strong reference marsquakes. Neither MQNet nor a manual review, using the same criteria used to confirm MQNet detections described in this manuscript, can confirm the large majority of these reported detections.…”
Section: Discussionmentioning
confidence: 99%
“…Sun and Tkalčić (2022) reported the discovery of 47 new LF events found during both the low‐ and high noise periods with template matching techniques using the S ‐wave waveform of nine strong reference marsquakes. Neither MQNet nor a manual review, using the same criteria used to confirm MQNet detections described in this manuscript, can confirm the large majority of these reported detections.…”
Section: Discussionmentioning
confidence: 99%
“…This slowing (dubbed ‛aging’) can be enhanced or reversed.” They suggest a new “creeping glass” model … “wherein environmental disturbances maintain soil in a perpetually fragile state.” Interestingly, these disturbances include thermal variations and variations in humidity (Bocquet et al., 2002) that are small compared to those measured with diurnal regularity on Mars. They would also include mechanical disturbances such as the expansion‐contraction activity in the adjacent or underlying bedrock discussed through much of this paper and impacts ranging from saltating sand grains to meteors as well as seismic activity on Mars (Sun & Tkalčić, 2022). Hence, this new “creeping glass” model bears on diverse surface processes on Mars, including downslope creep, and the micro‐relief evolution of eolian bedforms and regolith surfaces.…”
Section: Potential Geomorphic Implications Of Expansion‐contraction A...mentioning
confidence: 99%